2012
DOI: 10.1016/j.rbp.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences associated with drinking and driving in Brazil

Abstract: Factors , especially low schooling and leisure as a reason for travel, associated with drinking and driving were similar among regions, although certain region-specific features were observed. This information is important for aiming to reduce DUI in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
1
15
1
2
Order By: Relevance
“…The prevalence of DUIA found in previous studies varies according to geographical location, methodological differences, economic factors, and sociodemographic or behavioral characteristics of the drivers assessed [21,23,[36][37][38]. It is also influenced by country-level differences in legal BAC limits, enforcement, and alcohol use norms [23].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalence of DUIA found in previous studies varies according to geographical location, methodological differences, economic factors, and sociodemographic or behavioral characteristics of the drivers assessed [21,23,[36][37][38]. It is also influenced by country-level differences in legal BAC limits, enforcement, and alcohol use norms [23].…”
Section: Discussionmentioning
confidence: 93%
“…However, the study did not consider regional differences, nor did it analyze the factors associated with DUIA in each macroregion. Brazil is a country of continental scale, with cultural and economic heterogeneity among its macroregions; these differences may lead to differences in the prevalence and determinants of DUIA [21]. Understanding region-specific risk factors associated with DUIA is crucial for designing effective interventions to prevent RTIs [27].…”
mentioning
confidence: 99%
“…25 Furthermore, a Brazilian study investigated drinking and driving in the 27 Brazilian capitals and found that 2,410 of a total of 3,398 drivers interviewed had used alcohol over the past 12 months; of this subgroup, most were male (93.4%), drove cars or motorcycles, had a mean age of 36 years, and had completed high school. 26 With relation to alcohol consumption, 4.2% tested positive for BAC, and this number increased to 7.4% when the 6 hours preceding the interview were analyzed. 6 Our results are consistent with the aforementioned Brazilian studies.…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23][24][25][26][27] Combining the results obtained for license duration and education level, and assuming that these drivers have undertaken refresher driving courses, which specifically address drinking and driving, it can be inferred that these courses have not been effective enough to change the drivers' behaviors and to avoid recidivism. It would probably be necessary to implement preventive policies through psychoeducational campaigns aimed at the less educated population, as observed in other countries such as Australia (Transport Accident Commission, TAC; http://tac.vic.gov.au/).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores (88) alertam para a escassez de informações sobre como as diferenças regionais influenciam a eficácia dessas medidas públicas. Possivelmente, nas cidades do interior, as fiscalizações não sejam tão efetivas quanto nas capitais dos estados brasileiros.…”
Section: Variáveis Relacionadas àS Consequências Dos Acidentes De Trâunclassified